Reduction in left ventricular hypertrophy in hypertensive patients treated with enalapril, losartan or the combination of enalapril and losartan - Avanza Jr,Antônio Carlos (2000)
OBJECTIVE: To compare the regression of left ventricular hypertrophy in patients with moderate hypertension treated with enalapril, losartan or a combination of the two drugs at lower doses. METHODS: Patients of both sexes with moderate hypertension confirmed by ambulatory monitoring of arte-rial blood pressure and with left ventricular hypertrophy on echocardiogram were assigned to three groups: enalapril (35 mg/day, n=15), losartan (175 mg/day, n=15) and enalapril+losartan (15 mg+100 mg/day, n=16). The patients received the drugs for 10 months. RESULTS: The three therapeutic regimens were equally effective in reducing blood pressure and left ventricular mass index (LVMI, g/m²): 141±3.9 to 123±3.6 in the enalapril group (p<0.05), from 147±3.8 to 133±2.8 in the losartan group (p<0.05), and from 146±3.0 to 116±4.0 in the enalapril+losartan group (p<0.05). However, the percent reduction of LVMI was significantly greater (p<0.01) in the enalapril+losartan group (20.5±5.0%) than in enalapril (12.4±3.2%) and the losartan (9.1±2.1%) groups. Normalization of LVMI was obtained in 10 out of the 16 patients who received enalapril+ losartan, in 6 out of the 15 patients who received only enalapril and in 4 out of the 15 patients treated with losartan. CONCLUSION: The combination of an angiotensin-converting enzyme inhibitor and an angiotensin II receptor antagonist (AT1 receptor antagonist) in patients produced an additional effect on the reduction of left ventricular hypertrophy. This finding may depend on a more complete inhibition of the cardiac renin-angiotensin.